Detecting Outliers in Exponentiated Pareto Distribution - M. Jabbari Nooghabi (Journal of Sciences, Islamic Republic of Iran)
In this paper, we use two statistics for detecting outliers in exponentiated Paretodistribution. These statistics are the extension of the statistics for detecting outliers inexponential and gamma distributions. In fact, we compare the power of our test statisticsbased on the simulation study and identify the better test statistic for detecting outliers inexponentiated Pareto distribution. At the end, we describe an example from insurancecompany.